(untitled) (Research, Society and Development, 2022)
Vochysia divergens Pohl. is a tree species used in folk medicine, landscaping and reforestation. Its occurrence is recorded in the Amazon, Pantanal and Cerrado biomes and, despite these uses and its wide distribution, studies regarding its reproductive aspects are nonexistent. Thus, this research aimed to study the morphology of the pollen of V. divergens and evaluate the pollen viability and its meiotic index, as well as compare these descriptors in two natural populations, those of the Amazon and the Pantanal. To characterize the morphology, pollen grains were subjected to acetolysis and subsequently photographed, measured and classified. The meiotic index (MI) was estimated by counting post-meiotic products. Pollen viability was evaluated via colorimetric testing and in vitro germination. Pollen grains do not differ in morphology between populations and are classified as: large, 3-colporate, isopolar, subprolate, with a small and exine polar area that has a pattern of ornamentation that is perforated in the polar region. Via the colorimetric testing, the MI and the pollen viability were greater than 95% and only the MI differed between populations. Pollen germination was low and it was found that the presence of boric acid and absence of agar positively influence germination. The pollens of V. divergens have starch and lipids as a reserve substance. It can therefore be concluded that the species has reproductive stability, which is important in the effectiveness of fertilization and generation of new individuals for the formation of new generations, thus continuing the processes of forest restoration and maintenance of genetic variability. The information obtained regarding the pollen morphology can be used to support taxonomic, paleoclimatic and paleovegetational studies.